Probiotic Supplementation Improves Lipid Metabolism Disorders and Immune Suppression Induced by High-Fat Diets in Coilia nasus Liver - Jun Gao; Qi Mang; Yi Sun; Gangchun Xu (Biology)
High-fat diets (HFDs) usually trigger disruptions in lipid metabolic processes and immune suppression in fish. As an eco-friendly and potent additive, the inclusion of probiotics in fish diets ameliorates dysregulations in lipid metabolism, mitigates oxidative stress, and reduces inflammatory reactions triggered by HFDs. However, little current research has focused on the improvement of the hazards of HFDs in fish by probiotics. Therefore, we employed 4-dimensional data-independent (4D-DIA) proteomic analysis to investigate the mechanism of the protective impact of probiotics against HFD-induced hepatic injury in Coilia nasus between the HFD group and the probiotic supplementation in HFD (PHFD) group. Additionally, lipid accumulation and antioxidant indicators in the liver were also measured via Oil Red O staining and activity detection. Administration of probiotics markedly attenuated the hepatic concentrations of triglycerides (TG), cholesterol (CHO), and low-density lipoprotein cholesterol (LDL-C) in C. nasus subjected to HFDs. Furthermore, it significantly upregulated the expression of the differentially expressed proteins (DEPs) implicated in cholesterol metabolism and fatty acid oxidation, while concurrently downregulating the DEPs associated with fatty acid synthesis. Additionally, probiotic supplementation significantly reduced the aspartate aminotransferase (AST), alanine aminotransferase (ALT), and malondialdehyde (MDA) levels induced by HFDs. It also upregulated the activities of catalase (CAT) and superoxide dismutase (SOD). Probiotic supplementation significantly upregulated the DEPs related to antioxidants, while significantly downregulating the DEPs associated with inflammatory responses and autophagy. These findings suggested that probiotics ameliorated HFD-induced hepatic lipid accumulation in C. nasus by enhancing cholesterol metabolism and fatty acid oxidation, concomitantly with the suppression of fatty acid synthesis pathways. Additionally, probiotics protected against HFD-induced hepatic injury by enhancing antioxidant defenses and suppressing inflammation in C. nasus.